2021
DOI: 10.3390/pr9010085
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Artificial Intelligence into Biogas Plant Operation

Abstract: In the biogas plants, organic material is converted to biogas under anaerobic conditions through physical and biochemical processes. From supply of the raw material to the arrival of the products to customers, there are serial processes which should be sufficiently monitored for optimizing the efficiency of the whole process. In particular, the anaerobic digestion process, which consists of sequential complex biological reactions, requires improved monitoring to prevent inhibition. Conventional implemented met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 118 publications
0
15
0
1
Order By: Relevance
“…Te prominent energy sources are fossil fuels such as petroleum, diesel, kerosene, and liquefed natural gas, among others [1]. Te application of fossil fuels is accompanied by various environmental pollution, such as the greenhouse gas efect, depletion of the ozone layer, ecological challenges, and climate disturbance, among others [2,3]. It is in this connection that the need arises for other origins of alternative energy, which is capable of engineering sustainable development [4].…”
Section: Introductionmentioning
confidence: 99%
“…Te prominent energy sources are fossil fuels such as petroleum, diesel, kerosene, and liquefed natural gas, among others [1]. Te application of fossil fuels is accompanied by various environmental pollution, such as the greenhouse gas efect, depletion of the ozone layer, ecological challenges, and climate disturbance, among others [2,3]. It is in this connection that the need arises for other origins of alternative energy, which is capable of engineering sustainable development [4].…”
Section: Introductionmentioning
confidence: 99%
“…The anaerobic digestion process has four sequential stages: hydrolysis, acidogenesis, acetogenesis and methanogenesis. Since there are different kinds of microorganisms taking part in each stage of the anaerobic digestion process, supplying a suitable environment for a sustainable process is complex and makes it challenging monitor and control the process [3]. Any kind of anomaly from one of these stages can cause an unstable process.…”
Section: Introductionmentioning
confidence: 99%
“…With the harmonization of these parameters, it is possible to maintain an optimum environment for biological processes such as biogas production. To illustrate this, characteristics of the feedstock-such as composition, ratio of Total Organic Carbon (TOC) and Total Nitrogen (TN), particle size, total solids-as well as parameters during the process-including temperature, Organic Loading Rate (OLR), Hydraulic Retention Time (HRT), mixing, and pH-could be considered some of the operational parameters that affect the process capability [5][6][7][8][9][10][11]. Recent research has shown that temperature has a major effect on biogas production.…”
Section: Introductionmentioning
confidence: 99%
“…Use of statistics in any field with the help of Lean Six Sigma can lead to the reaping of the benefits of modern methods such as machine learning, predictive analytics, and big data. In this study, extensive literature research has been done for this topic [11,35]. For instance, De Clercq et al developed a machine learning model to predict biogas production and created a graphical user interface with the help of operational data from two industrial scale biogas plants in China [36].…”
Section: Introductionmentioning
confidence: 99%